STAN CYWILNOPRAWNEJ OCHRONY KONSUMENTA USŁUG UBEZPIECZENIOWYCH W POLSCE - Skorb, Marcin (Zeszyty Prawnicze, 2017)
Protection of Personal Data of Consumers of Insurance Services in Poland Summary The article analyses the regulations o f Polish civil law, which were introduced to protect a consumer of insurance services who, as a weaker party of a insurance agreement needs such protection. It presents main changes of the insurance law in this respect, introduced on M ay 01, 2004 as a part of the process of adapting Polish legal system to the EU legislation. Amongst other things, the author discusses the following issues: legal definition of a „consumer”, scope o f legal measures on protection of the insured, legal character of the general terms and conditions of the insurance agreements issued by insurance companies and forbidden contractual clauses. The author also suggests changes to these laws in order to improve them and make them more precise.